2008
DOI: 10.1103/physrevb.78.155107
|View full text |Cite
|
Sign up to set email alerts
|

Electronic properties of bulk and thin filmSrRuO3: Search for the metal-insulator transition

Abstract: We calculate the properties of the 4d ferromagnet SrRuO 3 in bulk and thin film form with the aim of understanding the experimentally observed metal-to-insulator transition at reduced thickness. Although the spatial extent of the 4d orbitals is quite large, many experimental results have suggested that electron-electron correlations play an important role in determining this material's electronic structure. In order to investigate the importance of correlation, we use two approaches which go beyond the convent… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
144
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(163 citation statements)
references
References 81 publications
(131 reference statements)
17
144
2
Order By: Relevance
“…14 which demonstrates that, although the localized states are not present in DFT calculations, a significantly broad component (∼40% of total intensity) arises in the convoluted Ru 4d PDOS at BE corresponding the reported data of the incoherent peak position. 9,14,25 It can be concluded that both the finite admixture of O 2p states in the dominant Ru 4d region and the asymmetric shape of the coherent Ru 4d feature, also obtained in some previous theoretical studies, 14,25,28,30 may contribute to the experimentally observed broad incoherent feature at ∼1.2-1.5 eV, thus suppressing the relative importance of localized surface states.…”
Section: High-energy Angle-resolved Photoemission Spectramentioning
confidence: 61%
See 2 more Smart Citations
“…14 which demonstrates that, although the localized states are not present in DFT calculations, a significantly broad component (∼40% of total intensity) arises in the convoluted Ru 4d PDOS at BE corresponding the reported data of the incoherent peak position. 9,14,25 It can be concluded that both the finite admixture of O 2p states in the dominant Ru 4d region and the asymmetric shape of the coherent Ru 4d feature, also obtained in some previous theoretical studies, 14,25,28,30 may contribute to the experimentally observed broad incoherent feature at ∼1.2-1.5 eV, thus suppressing the relative importance of localized surface states.…”
Section: High-energy Angle-resolved Photoemission Spectramentioning
confidence: 61%
“…The sharp peak near the Fermi level (A) and the broad one centered at ∼1.2 eV (B) are usually assigned to the coherent and incoherent parts of the spectral function, respectively. 9,14,25 The peaks D and E can be attributed to the mixture of Ru 4d and O 2p orbitals. The finite emission at 8-11 eV (negligible peak F) is due to the contaminations.…”
Section: High-energy Angle-resolved Photoemission Spectramentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the weakly dispersed t 2g states persist, and (Sr,Ca)Ru 2 O 6 remains metallic [N(E F )B4.36 eV per Ru atom] consistent with SOI calculations on bulk SrRuO 3 (ref. 35), where spin-orbit coupling also does not greatly alter the electronic structure.…”
Section: Resultsmentioning
confidence: 99%
“…13 Theoretically, the thermoelectric properties of SrTiO 3 /SrRuO 3 superlattices have been studied 14 and a metallic non-censtrosymmetric ruthenate double-perovskite oxide SrCaRu 2 O 6 with large thermopower anisotropy has been proposed. 15 Although the electronic, structural, magnetic and lattice dynamical properties of bulk SRO have already been extensively explored theoretically, [16][17][18][19][20][21] to the best of our knowledge, the thermoelectric aspects has not been reported. In spite of the fact that the thermoelectric performances of SRO appear relatively modest and do not make it a very promising candidate for technological applications, it remains a very important magnetic oxide compound.…”
Section: Introductionmentioning
confidence: 99%